A closed-cycle miniature Joule–Thomson cooler for cooling cold electronics. (5th June 2022) - Cao, Haishan; Meng, Qinghang; Tong, Xin; Wang, Chia-hsin; Liu, Biqiang; Wang, Xiaotao
Abstract: There is growing interest in operating electronics at low temperatures; however, the complexity of the cryogenic burden imposed by large coolers impedes the widespread usage of low-temperature electronics. In this study, we present a Hampson-type miniature Joule–Thomson (JT) cold stage driven by a linear compressor, and the performance of the cooler operating with a ternary mixture of methane, ethane and neopentane is investigated experimentally and numerically. Gas chromatography analysis shows that the composition of the circulated mixture is different from the charged mixture due to the liquid hold-up of neopentane. The cooler has a cold-end temperature of 143 K in steady state when operated between 0.15 MPa and 1.92 MPa, and a net cooling power of 198 mW at 145 K, 212 mW at 150 K, and 173 mW at 155 K. A dynamic numerical model is developed to predict cooler performance, and the feasibility of the numerical model is validated through the comparison between measured and calculated net cooling powers. The model can be used to estimate cooler performance at different operating conditions. This study is conducive to promote the widespread use of cryogenic electronics in the fields of military, space science, and biomedicine among others. Highlights: A miniature Joule–Thomson cooler driven by a linear compressor is built. A ternary mixture of methane, ethane and neopentane for 145 K cooling is proposed. The Joule–Thomson cooler achieves 143 K and has a cooling power of 198 mW at 145 K. A model of Hampson-type Joule–Thomson cooler operating with mixture is developed.